Germination, seedling growth and dry matter accumulation of Cola nitida in the nursery as affected by seed biotype colour and storage duration in dodecahedron pyramidal device - Boladale, S. B.; Oduntan, A.O.; Hammed, L.; Olasantan, F.O. (International Journal of Horticultural Science, 2026)
Long dormancy period and non-uniformity growth patterns of Cola nitida pose challenges for kola farmers, discouraging them from establishing kola plantations. Experiment was conducted at Federal University of Agriculture, Abeokuta, Ogun State, Nigeria to study the effects of seed colour and curing duration on germination, growth and dry matter yield of C. nitida. Experiment was 3 × 4 factorial, laid out in Completely Randomized Design. Treatments comprised seed colour (red, pink & white) and curing duration (12, 8, 4, and 0 weeks). The experiment had 12 treatments; each replicated three times. Data collected on germination, growth and dry matter were subjected to analysis of variance and means were separated using Duncan’s Multiple Range Test (P ≤ 0.05). Germination commenced at 4 WAS, on white, pink and red kola seeds stored for 8, 4 and 6 weeks with 10%, 6.66% and 3.33% respectively. At 8 WAS, white kola seeds stored for 12, 4 and 8 weeks had 93.3, 86.7 and 83.3% germination respectively. At 12 WAS, germination was completed for white kola 12-week stored in Dodecahedron Pyramidal Device (100%), while others range between 60.0 and 96.7%. White, pink and red kola seeds stored for 8, 4 and 12 weeks produced vigorous seedlings that were taller with more leaves than those of an un-stored seed at 18 and 20 WAS. In conclusion, white, pink and red kola (C. nitida) seed stored for 4, 8 and 12 weeks inside Dodecahedron Pyramidal Device resulted in rapid germination and improved morphological growth performance.